2007
DOI: 10.1111/j.1467-9280.2007.01928.x
|View full text |Cite
|
Sign up to set email alerts
|

Apparent Universality of Positive Implicit Self-Esteem

Abstract: For all the significant ps reported in this article, p rep > .979. Volume 18-Number 6 499 S. Yamaguchi et al.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

25
159
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 185 publications
(187 citation statements)
references
References 22 publications
(22 reference statements)
25
159
2
Order By: Relevance
“…As expected, the IRAPSE showed a significant effect for the self-positive response bias as indexed by significant one-sample t-tests in all diagnostic groups (ps ≤ 0.001). This is in line with (1) previous SE IRAP effects (e.g., [40] and [41]) and (2) findings for the 'universality' of self-positive implicit biases (e.g., [37]). An odd-even split-half procedure (applying the Spearman-Brown formula) was used to assess the reliability of the IRAP [42].…”
Section: Preliminary Analysessupporting
confidence: 92%
See 1 more Smart Citation
“…As expected, the IRAPSE showed a significant effect for the self-positive response bias as indexed by significant one-sample t-tests in all diagnostic groups (ps ≤ 0.001). This is in line with (1) previous SE IRAP effects (e.g., [40] and [41]) and (2) findings for the 'universality' of self-positive implicit biases (e.g., [37]). An odd-even split-half procedure (applying the Spearman-Brown formula) was used to assess the reliability of the IRAP [42].…”
Section: Preliminary Analysessupporting
confidence: 92%
“…During "inconsistent" blocks, the response contingencies were reversed. Trials were deemed to be "consistent" and "inconsistent" based on findings for the 'universality' of self-positive implicit biases (e.g., [37]). Fig.…”
Section: Implicit Relational Assessment Procedures (Irap)mentioning
confidence: 99%
“…Implicit self-esteem is a much researched construct of recent years (e.g., Koole, Dijksterhuis, & van Knippenberg, 2001 ;Yamaguchi et al, 2007 ). In a general sense, implicit self-esteem is defi ned as an automatic evaluation of the self that occurs nonconsciously and affects spontaneous reactions to self-relevant stimuli (Bosson, et al 2000 ).…”
Section: Improving Implicit Self-esteemmentioning
confidence: 99%
“…Much of the research conducted on the implicit measurement of self-esteem includes two categories (or samples): one that reflects the self and one that reflects the other (e.g., Vahey et al, 2009). These implicit measures, therefore, assess both attitudes toward the self and attitudes toward others (Karpinski, 2004;Yamaguchi et al, 2007) or, in the case of the IRAP, relational responding in regard to the self and with respect to someone (or some concept) outside of the self. The current studies used two samples that exclusively reflect responding in regard to the self, thereby eliminating the "other" comparison.…”
Section: Purpose Of Current Studiesmentioning
confidence: 99%
“…Furthermore, body-image satisfaction has been shown to be related to overall self-esteem and self-efficacy (Ip & Jarry, 2008;Mercurio & Landry, 2008;Verplanken & Velsvik, 2008). Given that previous research on the measurement of implicit beliefs about the self has found a weak correlation between implicit and explicit measures of self-esteem (Greenwald et al, 2002;Olson et al, 2007;Yamaguchi et al, 2007), it was hypothesized that women would have positive D IRAP scores and that the size of the D IRAP score would be significantly (but weakly) associated with greater body-image satisfaction and body-image acceptance and less internalization of the thin ideal. Furthermore, it was hypothesized that there might be differences in body satisfaction (measured implicitly) when comparing dieters to nondieters.…”
Section: Studymentioning
confidence: 99%